PENGARUH PERSONALISASI ALGORITMA TERHADAP ISLAMIC HUMAN CAPITAL MAHASISWA MUSLIM DI LAMONGAN DENGAN SELF-CONTROL SEBAGAI MEDIASI DALAM PERSPEKTIF UMER CHAPRA - Miko Tri Afandi; Syuhada'; Intan Ayu (LPPM STAI Muhammadiyah Probolinggo, 2026)
The transformation of algorithmic personalization technology on e-commerce platforms has an impact on the behavior and quality of Islamic human resources. This study aims to examine the effect of algorithmic personalization on the Islamic human capital of Muslim students in Lamongan, with self-control as a mediator, from Umer Chapra's perspective. The method used was quantitative, causal research. The study sample consisted of 102 people, determined using proportionate stratified sampling techniques with data analysis using PLS-SEM. The results of the study consist of: 1) algorithmic personalization has no significant effect on Islamic human capital. 2) algorithmic personalization has a significant effect on self-control. 3) self-control has a significant effect on Islamic human capital. 3) self-control is proven to significantly mediate the effect of algorithmic personalization on the Islamic human capital of Muslim students in Lamongan. These findings indicate that algorithmic personalization does not directly influence Islamic human capital, but rather through the role of self-control as a mediating variable. From Umer Chapra's perspective, strengthening self-control is a crucial factor in shaping the quality of an individual's Islamic human capital, ensuring that the use of digital technology remains aligned with Islamic values ​​and the goals of public welfare.